2017
DOI: 10.1371/journal.pgen.1006951
|View full text |Cite
|
Sign up to set email alerts
|

A SHH-FOXF1-BMP4 signaling axis regulating growth and differentiation of epithelial and mesenchymal tissues in ureter development

Abstract: The differentiated cell types of the epithelial and mesenchymal tissue compartments of the mature ureter of the mouse arise in a precise temporal and spatial sequence from uncommitted precursor cells of the distal ureteric bud epithelium and its surrounding mesenchyme. Previous genetic efforts identified a member of the Hedgehog (HH) family of secreted proteins, Sonic hedgehog (SHH) as a crucial epithelial signal for growth and differentiation of the ureteric mesenchyme. Here, we used conditional loss- and gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 71 publications
0
37
0
Order By: Relevance
“…Because expression of both genes was restricted to the inner layer of the UM, we questioned whether their expression depends on SHH or WNT signals emanating from the UE (Trowe et al, 2012;Yu et al, 2002). To address this question, we used a conditional pathway deletion approach, with a Tbx18 cre line, which mediates recombination in the entire UM starting from E11.5 (Airik et al, 2010;Bohnenpoll et al, 2013), and floxed alleles of the unique mediator of SHH signaling, Smo (Long et al, 2001), and of canonical WNT signaling, Ctnnb1 (Brault et al, 2001), as previously reported (Bohnenpoll et al, 2017b;Trowe et al, 2012). Loss of Smo had no effect on Tbx2 and Tbx3 expression in the UM at E12.5 (Fig.…”
Section: Tbx2 and Tbx3 Expression In The Um Depends On Canonical Wnt mentioning
confidence: 99%
See 1 more Smart Citation
“…Because expression of both genes was restricted to the inner layer of the UM, we questioned whether their expression depends on SHH or WNT signals emanating from the UE (Trowe et al, 2012;Yu et al, 2002). To address this question, we used a conditional pathway deletion approach, with a Tbx18 cre line, which mediates recombination in the entire UM starting from E11.5 (Airik et al, 2010;Bohnenpoll et al, 2013), and floxed alleles of the unique mediator of SHH signaling, Smo (Long et al, 2001), and of canonical WNT signaling, Ctnnb1 (Brault et al, 2001), as previously reported (Bohnenpoll et al, 2017b;Trowe et al, 2012). Loss of Smo had no effect on Tbx2 and Tbx3 expression in the UM at E12.5 (Fig.…”
Section: Tbx2 and Tbx3 Expression In The Um Depends On Canonical Wnt mentioning
confidence: 99%
“…At E11.5, SHH activates a SMO-dependent pathway in the UM that is required for survival of cells in the outer layer, for proliferation and SMC differentiation of cells of the inner layer, and also for urothelial proliferation and differentiation. The proliferation and differentiation functions of SHH signaling are mediated by the forkhead transcription factor FOXF1, which, in turn, induces expression of and synergizes with BMP4 in SMC differentiation (Bohnenpoll et al, 2017b;Mamo et al, 2017). At E12.5, WNT7B and WNT9B activate the canonical WNT pathway in cells of the inner mesenchymal layer, disruption of which results in reduced proliferation and failed SMC differentiation of these cells, and expansion of the adventitial fate to the inner layer (Trowe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To identify molecular changes that may cause defective SMC differentiation in Gata2cKO ureters, we screened (using in situ hybridisation) for activity of pathways and expression of genes that have been implicated in this programme: Ptch1 , target of SHH signalling ; Bmp4 ; Id2 , target of BMP signalling ; Axin2 , target of WNT signalling ; Rarb , target of RA signalling ; and the transcription factor genes Foxf1 , Tbx18 , Tszh3 , and Sox9 . At E14.5, all of these genes were expressed in the inner UM of mutant ureters as in the control except for Tbx18 , Tshz3 , and Rarb , which were up‐regulated (supplementary material, Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…Ureters were explanted on 0.4 μm polyester membrane Transwell supports (#3450; Corning Inc, Lowell, MA, USA) and cultured at the air–liquid interface as previously described . BMS493 (#3509; Tocris BioScience, Minneapolis, MN, USA) and RA (#0695; Tocris) were dissolved in DMSO and added to the medium at a final concentration of 1 μ m .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation